2020
DOI: 10.1186/s12880-020-00479-y
|View full text |Cite
|
Sign up to set email alerts
|

Discriminative pattern of reduced cerebral blood flow in Parkinson’s disease and Parkinsonism-Plus syndrome: an ASL-MRI study

Abstract: Background: Accurate identification of Parkinson's disease (PD) and Parkinsonism-Plus syndrome (PPS), especially in the early stage of the disease, is very important. The purpose of this study was to investigate the discriminative spatial pattern of cerebral blood flow (CBF) between patients with PD and PPS. Methods: Arterial spin labeling (ASL) perfusion-weighted imaging was performed in 20 patients with PD (mean age 56.35 ± 7.56 years), 16 patients with PPS (mean age 59.62 ± 6.89 years), and 17 healthy contr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…Of these, the cerebellum has low susceptibility to age‐related atrophy, minimal changes in metabolism, and CBF, and, from an amyloid perspective, demonstrates low or absent amyloid plaque burden. However, studies have reported a lowered or no difference in cerebellar perfusion in PD compared to controls or relative increases in cerebellar metabolism associated with cognitive ability in PD 80–82 . Systematic decreases or increases in the reference region will lead to artefactual SUVR increases and decreases, respectively 83 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, the cerebellum has low susceptibility to age‐related atrophy, minimal changes in metabolism, and CBF, and, from an amyloid perspective, demonstrates low or absent amyloid plaque burden. However, studies have reported a lowered or no difference in cerebellar perfusion in PD compared to controls or relative increases in cerebellar metabolism associated with cognitive ability in PD 80–82 . Systematic decreases or increases in the reference region will lead to artefactual SUVR increases and decreases, respectively 83 .…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have reported a lowered or no difference in cerebellar perfusion in PD compared to controls or relative increases in cerebellar metabolism associated with cognitive ability in PD. 80 , 81 , 82 Systematic decreases or increases in the reference region will lead to artefactual SUVR increases and decreases, respectively. 83 While the whole cerebellum was suitable for the current study, future work may evaluate several reference regions, such as a combined cerebellum and pons.…”
Section: Discussionmentioning
confidence: 99%
“…It is the central area of Broca’s sports language area and participates in the evaluation of sensory and emotional information [ 23 ]. Research has shown that there is a certain connection between this area and Parkinson’s syndrome [ 24 ]. Yu et al reported that the ALFF value of the left IFG was significantly reduced in patients with diabetic retinopathy [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The IFG pars triangularis is also associated with concept selection by means of solving competitions between active representations ( 51 ). Cheng et al ( 52 ) reported that there is some connection between the IFG pars triangularis and Parkinson's syndrome. Qi et al ( 53 ) pointed out that children's language performance is related to the asymmetric changes of cortical thickness in the IFG pars triangularis.…”
Section: Discussionmentioning
confidence: 99%